2012
DOI: 10.1111/j.1365-2621.2011.02912.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of two Williopsis yeast strains on the volatile composition of mango wine

Abstract: Summary The aim of the research was to study the volatile composition of mango wine fermented with two Williopsis yeast strains: Williopsis saturnus var. mrakii NCYC500 and W. staurnus var. suaveolens NCYC2586. Thirty terpenoids, twenty‐six esters, ten alcohols, nine acids, seven aldehydes and ketones, two ethers, two phenols and one sulphur compound were identified in the mango wine fermented with strain NCYC500, while twenty‐seven terpenoids, thirty esters, eleven alcohols, eight acids, eight aldehydes and k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 24 publications
1
22
1
Order By: Relevance
“…Other researchers have also observed the comparatively slower growth rates of Williopsis yeasts (17,18). It has been shown that the intensity of fermentation (defi ned as the average number of days elapsing between inoculation of the glucose fermentation tube and the reduction of gas volume in the insert) with W. saturnus var.…”
Section: Yeast Growth Total Soluble Solids and Ph Changesmentioning
confidence: 98%
“…Other researchers have also observed the comparatively slower growth rates of Williopsis yeasts (17,18). It has been shown that the intensity of fermentation (defi ned as the average number of days elapsing between inoculation of the glucose fermentation tube and the reduction of gas volume in the insert) with W. saturnus var.…”
Section: Yeast Growth Total Soluble Solids and Ph Changesmentioning
confidence: 98%
“…mrakii NCYC500 (National Collection of Yeast Cultures, Norwich, UK) and S. cerevisiae MERIT.ferm (Chr.-Han., Denmark) were used in this study. The preculture and mango juice preparation were shown in the previous report (Li et al, 2012). A ratio screening (Saccharomyces:Williopsis = 1:1, 1:10, 1:100 and 1:1000) was carried out to determine the ratio that would be used in subsequent mixed-culture fermentation.…”
Section: Yeast Strain Juice Preparation Pre-culture and Fermentationmentioning
confidence: 99%
“…However, there is very little information on mango wine production using mixed-culture fermentation (SAdineni et al, 2011). W. mrakii, formerly known as Hansenula mrakii, is an efficient producer of acetate esters (Li et al, 2012). The yeast has been inoculated to improve the fruity character of Japanese sake (Inoue et al, 1997), grape wine (Erten & TAnguLer, 2010) and papaya wine (Lee et al, 2010).…”
mentioning
confidence: 99%
“…mrakii (formerly Hansenula mrakii) yeast strains are known as efficient producers of fruity or floral acetate esters such as isoamyl acetate and 2-phenylethyl acetate important to wine aroma (Yilmaztekin et al, 2008;Li et al, 2012) and the strain was used in sake to improve its fruity character (Inoue et al, 1994). Some researchers have started to co-culture Saccharomyces and Williopsis to improve wine fruitiness and complexity (Erten and Tanguler, 2010;Lee et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…) and demonstrated the optimization effects on the production of ethanol, glycerol, and volatile acidity. Li et al (2011Li et al ( , 2012 noted the differentiation of the chemical and volatile compositions of mango wines fermented with monocultures of S. cerevisiae and Williopsis saturnus var. mrakii (W. mrakii).…”
Section: Introductionmentioning
confidence: 99%